2018
DOI: 10.1520/jte20170057
|View full text |Cite
|
Sign up to set email alerts
|

Charpy Impact Test Methods for Cementitious Composites: Review and Commentary

Abstract: Several researchers have recently employed the Charpy method to characterize the high strain rate mechanical strength of cementitious composites. This paper provides a critical review of existing applications of the Charpy method for impact testing of cementitious composites. Studies have employed various specimen sizes and geometries. Additionally, some studies have tested notched specimens while others have tested plain. Furthermore, varying methods of normalization result in results reported in a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…Moreover, results between different test set-ups and studies are difficult to compare as they are characterised by a wide range of properties, such as the impact velocity, the loading configuration and the specimen geometry [49][50][51]. For those reasons and due to the low reproducibility of a drop-weight impact test and the limited results, the used impact test is based on the Charpy impactor typically used for metals and plastics [49,52].…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, results between different test set-ups and studies are difficult to compare as they are characterised by a wide range of properties, such as the impact velocity, the loading configuration and the specimen geometry [49][50][51]. For those reasons and due to the low reproducibility of a drop-weight impact test and the limited results, the used impact test is based on the Charpy impactor typically used for metals and plastics [49,52].…”
Section: Test Methodsmentioning
confidence: 99%
“…In general, the smallest dimension of the test specimen is at least five times the maximum aggregate size, in this case, 3 mm. Additionally, the length of the used fibres is limited to half the minimum specimen dimension in order to achieve a homogenous mixture [51,53]. Dimensions that correspond with those recommendations do not fit the available test equipment, and therefore, specimens of 100 mm x 11 mm x 7 mm are prepared.…”
Section: Test Methodsmentioning
confidence: 99%
“…All of the specimens were cured in the water under laboratory conditions (20 ± 20 • C, 50 ± 5% R.H). The Charpy specimen was proposed in the form of a 10 × 10 × 50 mm v-notched bar [15]. The specimen dimensions are clarified in Figure 1, where β = 45 • -90 • , a = 2 mm, w = B = 10 mm, L = 50 mm.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…It is not only utilized and standardized for testing metallic materials (ASTM E23, ISO 148) [ 8 , 9 ] or plastic materials (ASTM D6110, ISO 179) [ 10 , 11 ], but also is applied to composites, ceramics, and polymers [ 12 , 13 , 14 ]. In particular, the literature review shows the energy absorption capacity of cement-based materials as measured by the Charpy pendulum impact test [ 15 ]. Hakamy et al [ 16 ] found good interfacial bonding between the fibers and nanomatrix, and observed an increase of 23% in the impact strength of a hemp fabric-reinforced nanoclay–cement composite compared to that of a hemp fabric-reinforced cement composite.…”
Section: Introductionmentioning
confidence: 99%
“…For concrete, on the other hand, the drop weight method based on the principles given in the ACI 544 standard is widely used [7]. While fracture energy and impact resistance are determined quantitatively in Charpy and Izod methods, the drop weight method uses the number of weight drops as the basis for determining when the first crack occurs in the concrete sample, and then the number of cracks increases such that the sample loses its bearing capacity [8]. Recently, studies have been concentrated on the applicability of the Charpy method to directly determine the energy required to fracture concrete as a result of an impact [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%